Development of Teaching Modules Based on Problem Based Learning Integrated with Scientific Literacy on Acid Base Material - Ilham Septiana; Ratna Sari Siti Aisyah; Nela Fatmasari (Universitas Negeri Gorontalo, 2025)
Scientific literacy in Indonesia is not yet a major concern, this is proven by data from the Program for International Student Assessment (PISA) which shows that Indonesia's scientific literacy ranking is in 71st position out of 77 countries. The Problem Based Learning (PBL) model is a learning model that can improve students' scientific literacy skills in explaining problems in everyday life, including those related to acids and bases, based on scientific data. The PBL model is suitable for application in an independent curriculum. One of the problems faced by educators in the independent curriculum is a lack of understanding in compiling teaching modules. The aim of this research is to develop a teaching module based on problem-based learning integrated with scientific literacy in acid-base material. This research is research and development research with the ADDIE model (analysis, design, development, implementation, evaluation). Data collection techniques used validation tests from material experts, media experts and limited trials on 30 students. Analysis of validation data using the Aiken's formula with a V table value of 0.79. The research results show that the Vcount value â‰¥ Vtable, the material validation Vcount value is 0.88, while the media validation value is 0.90 so it can be declared valid. The limited trial for students obtained a percentage score of 91.18% in the